Bone talk - Gourlay, Candy (David Fickling Books, Scholastic Inc., 2019)
In a remote village in the Philippines at the end of the nineteenth century, ten-year-old Samkad must deal with a separation from his best friend before unknown American enemies bring war and destruction.